El deber de virtuosismo en el periodista: persona, información y prudencia - Atarama Rojas, Tomás Ricardo (Mercurio Peruano, 2013)
The duty of virtue involves constant search in journalist to be better to achieve higher levels of quality in journalism as a result of personal growth. This article will develop three essential points in the education of journalists. Initially, we study the formation of virtues, then, we will delve into how to encourage prudence in an atmosphere of freedom, and finally we will combine the concepts of person, information and prudence, as elements that promote journalism excellence.
Keywords: communication, person, information, ethics, journalism.